2019
DOI: 10.1186/s12871-019-0811-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative sore throat and subglottic injury after McGrath® MAC videolaryngoscopic intubation with versus without a stylet in patients with a high Mallampati score: a randomized controlled trial

Abstract: Background A tracheal tube stylet can be used to assist successful tracheal intubation, especially during videolaryngoscopic intubation because videolaryngoscopes with a Macintosh-type blade such as McGrath® MAC videolaryngoscope have more acute angle than conventional Macintosh laryngoscope. However, the use of a stylet during tracheal intubation can raise concerns about stylet-induced postoperative airway complications, such as sore throat, subglottic injury, and hoarseness. In this study, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Therefore, POST is not only a postoperative complication but also an intubation- and extubation-related complication. These procedures might produce subglottic injury and upper airway mucosal injury that induce POST ( 20 ). Although POST appears short-lived and usually resolves within a week or less, it should be viewed as a preventable side effect in the era of early enhanced recovery surgery in which patients return to full function as early as possible ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, POST is not only a postoperative complication but also an intubation- and extubation-related complication. These procedures might produce subglottic injury and upper airway mucosal injury that induce POST ( 20 ). Although POST appears short-lived and usually resolves within a week or less, it should be viewed as a preventable side effect in the era of early enhanced recovery surgery in which patients return to full function as early as possible ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this was not proven in our study, some previous articles have described tracheal injury by a stylet. 9 , 11 , 13 17 Therefore, we evaluated the efficacy of the lightwand tip located 1 cm below the vocal cords for lightwand intubation and assessed the corresponding point for the position of the lightwand tip on the patient’s neck.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, some reports indicated that use of a stylet could cause tracheal injury. 9 , 11 , 13 17 We considered that such tracheal injury due to use of a stylet may result from over-insertion of the stylet into the tracheal tube before intubation, rapid and powerful advancement of the combined tracheal tube and stylet into the trachea, or unnecessary deep insertion of the combined tracheal tube and stylet into the trachea. The lightwand is a type of stylet often referred to as a lighted stylet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, a recent study demonstrated increased anterior tracheal tissue injury when rigid stylets were used with VL as opposed to no stylet. 15 One method to overcome the challenge of airway navigation is combining the use of VL with FOB. Multiple studies have demonstrated this 'combined technique' to facilitate intubation of the difficult airway.…”
Section: Discussionmentioning
confidence: 99%